APPLICATIONS AND IMPLICATIONS OF OUTDOOR STUDY METHODS ON GEOGRAPHY LEARNING (LITERATURE REVIEW) - Nyokro Mukti Wijaya (Journal Learning Geography, 2021)
The aim of this study were (1) to provide guidance on the application of the otudoor learning method in geography learning  and (2) to describe the application of the outdoor study method in geography learning. The research method used is a descriptive type of research with a qualitative approach. The research data is used using literature review. The things that are excluded in the article to be reviewed include (1) the amount of information, (2) quality of information, (3) accuracy of data and facts, (4) source of writing, and (5) citations. Meanwhile, the data that will be presented include (1) the application of outdoor studies, (2) implications of outdoor studies, and (3) updating of information. The results obtained are (1) outdoor learning applications in geography learning can be done with steps  of planning, preparation, , field observations, preparation of reports, and presentation of results. (2) the implications of outdoor learning in geography learning include improving learning outcomes, writing scientific papers, spatial intelligence, and learning for students.